MicroEcoTools: An R package for comprehensive theoretical microbial ecology analysis - Soheil A. Neshat; Ezequiel Santillan; Stefan Wuertz (Methods in Ecology and Evolution)
Abstract Ecological theory aids in understanding how disturbances affect ecosystems. However, experimental data are often complex, with multiple post‐disturbance theories potentially applying simultaneously to the same ecosystem. This emphasizes the need for tools to experimentally test these theoretical predictions. We introduce MicroEcoTools, an R package designed to test ecological framework predictions using microbial community data. It assesses microbial diversity and evaluates the relative impacts of stochastic and deterministic assembly mechanisms through a taxa‐based null model approach for replicated designs. Furthermore, the package allows application of Grime's trait‐based life‐history categories—competitor, stress‐tolerant and ruderal (CSR)—to taxa, functional traits and ecosystem functions within microbial communities. MicroEcoTools also includes relevant statistical tests, numeric simulations and publicly available datasets for demonstration. To demonstrate MicroEcoTools' functionality, we applied the package to experimental data from microcosm‐scale perturbation experiments on an activated sludge microbial ecosystem (included in the R package). This enabled us to assess assembly mechanisms and assign CSR categories. Results generated by MicroEcoTools closely aligned with previous findings from manual analysis. In conclusion, MicroEcoTools facilitates the application of ecological frameworks, including community assembly mechanisms, diversity analysis, and life‐history strategies, to microbial ecosystems under disturbance. This R package, along with its source code, can be freely accessed on GitHub at https://www.github.com/Soheil‐A‐Neshat/MicroEcoTools.